Central-Bank Credibility: Why Do We Care? How Do We Build It? - Blinder, Alan S (American Economic Review, 2000)
Central bank credibility plays a pivotal role in much of the modern literature on monetary policy, yet it is difficult to measure or even assess objectively. A survey of central bankers was conducted to determine their attitudes on two important issues: why credibility matters, and how credibility can be built. The central bankers' answers are compared with the responses of NBER-affiliated macro and monetary economists. The two groups agree much more than they disagree. They are particularly united in their evaluations of ways to make a central bank credible – assigning high ratings to the central bank's track record and low ratings to theoretical ideas like precommitment and incentive-compatible contracts.